A low-cost, high-performance oxide solid electrolyte and its preparation method and use

By adopting low-cost oxide solid electrolytes such as LiAlSiO4, Li2ZnSiO4, LiGaZrO4, etc., combined with high-temperature solid-phase preparation technology, the problem of high cost of lithium lanthanum zirconium oxygen solid electrolytes is solved, and high-performance and low-cost replacement in all-solid-state batteries is achieved The solution improves the ionic conductivity and electrochemical window of the electrolyte.

CN113299977BActive Publication Date: 2024-12-17GUANGZHOU TINCI MATERIALS TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202010106678.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-02-21
Publication Date
2024-12-17
Estimated Expiration
2040-02-21

AI Technical Summary

Technical Problem

The existing lithium lanthanum zirconium oxygen (LLZO) solid electrolytes contain rare earth elements, which leads to high costs and is difficult to achieve low-cost and high-performance alternatives, limiting the commercial development of all-solid-state batteries.

Method used

Low-cost oxide solid electrolytes, such as LiAlSiO4, Li2ZnSiO4, LiGaZrO4, etc., are prepared by high-temperature solid phase method, including wet ball milling, presintering, crushing, tableting and high-temperature sintering, to ensure high ionic conductivity and electrochemical The window is wide.

Benefits of technology

It realizes a low-cost solid electrolyte with performance comparable to LLZO, reduces production costs, and is easy to obtain raw materials. It can replace LLZO in all-solid-state batteries, providing high ionic conductivity and wide electrochemical windows.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002388692740000101
    Figure BDA0002388692740000101
Patent Text Reader

Abstract

The present invention discloses an oxide solid electrolyte and a preparation method and use thereof. The oxide solid electrolyte includes a crystalline state, and the chemical composition includes LiAlSiO4, Li2ZnSiO4, LiGaZrO4, LiBiGeO4, LiGa5O8, LiGaO2, Li5GaO4, Li4Zn3Ga2Ge2O 12 、Li8Zn3Ga2Ge2O 14 or Li 12 Zn3Ga2Ge2O 16 Any one of the above. The method comprises: 1) weighing raw materials according to the molar ratio of the oxide solid electrolyte chemical formula, mixing and wet ball milling; 2) evaporation and drying; 3) pre-sintering; 4) crushing, tableting, and re-sintering. The present invention has a simple process and low production cost. The obtained oxide solid electrolyte has high ionic conductivity and wide electrochemical window, and is an ideal substitute for LLZO solid electrolyte material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolytes, and in particular to an oxide solid electrolyte, a preparation method and use thereof, and in particular to a low-cost, high-performance oxide solid electrolyte, a preparation method and use thereof. Background Art

[0002] All-solid-state batteries are the inevitable development trend of battery technology in the future, and solid-state electrolytes, as the core materials of all-solid-state batteries, have become a battleground. Simply put, a solid-state electrolyte is a superionic conductor that replaces the role of electrolytes and diaphragms in traditional lithium-ion batteries in all-solid-state batteries, and is a functional substance that conducts ions and connects positive and negative electrodes. To realize the application of solid-state electrolytes in all-solid-state batteries, we must first have good solid-state electrolytes, and secondly, solve the matching problem between solid-state electrolytes and positive and negative electrodes. Ionic conductivity and interface problems are the two most critical problems of solid-state electrolytes, and finding a solid-state electrolyte with good comprehensive performance has become the top priority.

[0003] Solid electrolytes can completely solve the flammable and explosive safety hazards of liquid electrolytes by replacing the organic electrolytes in existing lithium-ion batteries. However, not every substance can become an ideal solid electrolyte. It is subject to certain conditions; the diverse requirements make the search for solid electrolytes an ongoing topic. Since 1957, people have been constantly looking for solid electrolytes; but so far, there is still no one that can be called a perfect solid electrolyte. The current mainstream solid electrolytes are polymers, oxides and sulfides, and lithium lanthanum zirconium oxide (Li7La3Zr2O 12 LLZO) is a typical representative of oxide solid electrolytes and is regarded as the most commercially promising solid electrolyte due to its outstanding comprehensive performance.

[0004] CN105406117 A discloses an all-solid-state lithium ion electrolyte material Li7La3Zr2O 12 The preparation method thereof comprises the following steps: (1) mixing and grinding LiNO3, LiOH, La2O3 and ZrO2; (2) calcining the ground mixture under an inert atmosphere to obtain the all-solid-state lithium ion electrolyte material Li7La3Zr2O 12 The method has short calcination time, low temperature, simple operation, avoids the introduction of non-reactant impurities, and the product has a nanosheet layered structure and a high specific surface area, thereby greatly improving its ion conductivity at room temperature.

[0005] CN 103594725 A discloses a lithium ion battery solid electrolyte Li7La3Zr2O 12The invention discloses a preparation method thereof, comprising the following steps: (1) mixing a lithium source compound, a lanthanum source compound and a zirconium source compound in a molar ratio of Li, La and Zr of 7 to 8:3:2, and then placing the mixture in a dispersion medium for ball milling; (2) drying the obtained mixture at 95 to 105° C. for 8 to 12 hours, and then grinding the mixture into powder to obtain a precursor, and mixing the precursor with glucose or sucrose uniformly, and then pre-calcining the precursor, wherein the pre-calcining temperature is 500 to 800° C., and the pre-calcining time is 12 to 24 hours; (3) dispersing the pre-calcined precursor in a dispersion medium, and then ball milling the precursor again, and then mixing the precursor with glucose or sucrose uniformly, and then calcining the precursor, and then grinding the precursor to obtain Li7La3Zr2O 12 The sample is calcined at a temperature of 600 to 900°C for 24 to 36 hours.

[0006] CN 105489930 A discloses a molten salt method for preparing a solid lithium ion electrolyte material Li7La3Zr2O 12 The method comprises the following steps: (1) mixing and grinding LiNO3, CH3COOLi, La2O3 and ZrO2, wherein LiNO3 and CH3COOLi are used as molten salt and lithium source, and the mass ratio of LiNO3 to CH3COOLi is 1:(1.5-1.7); (2) calcining the ground mixture at 700-800°C for 3-5 hours under an inert atmosphere and cooling it to room temperature naturally to obtain the solid lithium ion electrolyte material Li7La3Zr2O 12 However, since La is a rare earth element, LLZO solid electrolyte still has the problem of high cost. Therefore, the development and research of low-cost, high-performance solid electrolytes is the key to the successful commercialization of all-solid-state batteries. Summary of the invention

[0007] In view of this, the purpose of the present invention is to provide an oxide solid electrolyte and a preparation method and use thereof, in particular to provide a low-cost, high-performance oxide solid electrolyte and a preparation method and use thereof. The oxide solid electrolyte of the present invention is comparable to LLZO in performance, and has low cost and readily available raw materials, and can replace LLZO in all-solid-state batteries.

[0008] The "low cost and high performance" mentioned in the present invention means that the oxide does not contain expensive rare earth elements and the ionic conductivity is ≥1×10 -3 S / cm solid electrolyte.

[0009] To achieve the above object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides an oxide solid electrolyte, wherein the oxide solid electrolyte includes a crystalline state, and the chemical composition of the oxide solid electrolyte includes LiAlSiO4, Li2ZnSiO4, LiGaZrO4, LiBiGeO4, LiGa5O8, LiGaO2, Li5GaO4, Li4Zn3Ga2Ge2O 12 、Li8Zn3Ga2Ge2O 14 or Li 12 Zn3Ga2Ge2O 16 Any one of .

[0011] The oxide solid electrolyte of the present invention is preferably used in a single species, because the presence of grain boundaries between two or more species of oxide solid electrolytes deteriorates their performance.

[0012] When a single type of target product is actually prepared, there may be trace impurities, which do not affect the high ionic conductivity and wide electrochemical window of the oxide solid electrolyte of the present invention. Preferably, the impurity content is less than 0.05% or even lower to obtain excellent performance closer to that of a single type of specific oxide.

[0013] Among the oxide solid electrolytes provided by the present invention, LiAlSiO4, Li2ZnSiO4, LiGaZrO4 and LiBiGeO4 belong to simple cubic crystal structures and have one-dimensional ion transmission channels; LiGa5O8, LiGaO2 and Li5GaO4 belong to lithium fast ion conductor crystal structures and have two-dimensional ion transmission channels; Li4Zn3Ga2Ge2O 12 、Li8Zn3Ga2Ge2O 14 and Li 12 Zn3Ga2Ge2O 16 It has a garnet crystal structure and a three-dimensional ion transport channel. The above oxide solid electrolyte has the remarkable characteristics of high ion conductivity and wide electrochemical window. It is an ideal solid electrolyte that can perfectly replace LLZO in all-solid-state batteries.

[0014] As a preferred technical solution of the oxide solid electrolyte described in the present invention, the chemical composition of the oxide solid electrolyte is any one of LiGaZrO4, LiGa5O8, LiGaO2 or Li5GaO4.

[0015] As a preferred technical solution of the oxide solid electrolyte of the present invention, the oxide solid electrolyte includes LiGaZrO4, and the molar ratio of Li, Ga and Zr is 1:1:1. The reason for the preference is that LiGaZrO4 can not only meet the requirements of low cost and high performance, but also take into account the compatibility of positive and negative electrodes, especially the stability to the lithium negative electrode.

[0016] Preferably, the raw material source of the oxide solid electrolyte is any one or a combination of at least two of carbonates, oxides or hydroxides of respective chemical compositions, such as Li2CO3, LiOH, Li2O, Ga2(CO3)3, Ga2O3, Ga(OH)3, Zr(CO3)2, ZrO2 or Zr(OH)4.

[0017] In a second aspect, the present invention provides a method for preparing the oxide solid electrolyte as described in the first aspect, wherein the method is a high-temperature solid phase method, comprising:

[0018] (1) weighing raw materials according to the molar ratio of the oxide solid electrolyte chemical formula, mixing and wet ball milling;

[0019] (2) evaporative drying;

[0020] (3) Pre-sintering;

[0021] (4) Crushing, tableting and re-sintering.

[0022] In the method of the present invention, the pre-sintering in step (3) is an essential step. If the pre-sintering is not performed, it will lead to incomplete reaction between oxides or excessively large grains, which will reduce ionic conductivity.

[0023] The method of the present invention is a high-temperature solid-phase two-step method, which performs high-temperature two-step sintering on oxide raw materials, has a simple preparation process, and can produce an oxide solid electrolyte with excellent performance.

[0024] Preferably, the raw material in step (1) is any one of carbonate, oxide or hydroxide or a combination of at least two thereof. The raw material is a raw material corresponding to the chemical composition of the target product, for example, when the target product is LiAlSiO4, the raw material is a carbonate, oxide or hydroxide of the corresponding elements Li, Al and Si.

[0025] Preferably, the wet ball milling in step (1) comprises: mixing the raw materials, using alcohol as a dispersion medium and ball milling balls as ball milling media, and performing wet ball milling.

[0026] Preferably, the wet ball milling time in step (1) is 2 to 8 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours, 5.5 hours, 6 hours, 7 hours or 8 hours.

[0027] Preferably, the pre-sintering temperature in step (3) is 700-900°C, such as 700°C, 725°C, 750°C, 800°C, 850°C or 900°C, etc., preferably 800-900°C.

[0028] Preferably, the pre-sintering time in step (3) is 2 to 8 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours, 5.5 hours, 6 hours, 7 hours or 8 hours.

[0029] Preferably, the crushing in step (4) is high-energy crushing, preferably high-energy ball milling. High-energy mechanical ball milling is a combination of physical and chemical methods. Its basic principle is that during the ultrafine grinding of crystalline materials, the mechanical force can activate their chemical activity, so that reactions that usually need to be carried out at high temperatures can be carried out at lower temperatures. High-energy mechanical ball milling has the advantages of easy operation, simple process, solvent-free, high efficiency and energy saving, narrow particle size distribution, and reduced sintering temperature, and can achieve uniform dispersion and mixing of different components.

[0030] Preferably, the tabletting pressure in step (4) is 190-220 MPa, such as 190 MPa, 200 MPa, 205 MPa, 210 MPa, 215 MPa or 220 MPa. The holding time is 5-10 min. The tabletting pressure and holding time have a great influence on the structure and performance of the oxide solid electrolyte of the present invention. In order to obtain a good tabletting effect and have the best ionic conductivity after sintering, the above pressure and holding time are preferred.

[0031] Preferably, the sintering temperature in step (4) is 1100-1300°C, such as 1100°C, 1150°C, 1200°C, 1250°C, 1280°C or 1300°C, etc.; the sintering time is 2-8h, such as 2h, 3h, 4h, 5h, 5.5h, 6h, 7h or 8h, etc. If the temperature is lower than 1100°C, the sintering driving force will be insufficient, the reaction will be incomplete and the ionic conductivity will be affected; if the temperature is higher than 1300°C, the oxide will volatilize seriously, resulting in incorrect ratio and reduced ionic conductivity.

[0032] Preferably, the sintering temperature in step (4) is 200-400°C higher than the pre-sintering temperature in step (3). The purpose of this setting is that the pre-sintering allows the reactants to fully contact each other to form a preliminary crystal structure. After subsequent crushing and tableting, sintering at a higher temperature is performed to improve the reaction intimacy and form a dense crystal structure, thereby obtaining ideal ionic conductivity.

[0033] As a further preferred technical solution of the method of the present invention, the method comprises the following steps:

[0034] (1) weighing raw materials according to the molar ratio of the oxide solid electrolyte chemical formula, mixing, using anhydrous ethanol as a dispersion medium and zirconium oxide grinding balls as a ball milling medium, and wet-milling for 2 to 8 hours to obtain a slurry;

[0035] (2) evaporative drying;

[0036] (3) Pre-sintering in a sintering furnace at 700-900°C for 2-8h;

[0037] (4) The pre-sintered material is crushed into powder by high-energy ball milling, pressed into tablets under a pressure of 190 to 220 MPa for 5 to 10 minutes, and then placed in a sintering furnace at 1100 to 1300°C for 2 to 8 hours.

[0038] In a third aspect, the present invention provides a use of the oxide solid electrolyte as described in the first aspect in a solid-state battery. The oxide solid electrolyte of the present invention can be used alone or in combination with other types of solid electrolytes. The use alone can be a single type or a combination of types.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The oxide solid electrolyte of the present invention has the remarkable characteristics of high ion conductivity and wide electrochemical window. Moreover, the raw materials are easily available and the cost is low. It is an ideal solid electrolyte and can perfectly replace the application of LLZO in all-solid-state batteries. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0042] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be further clearly and completely described below in combination with the embodiments of the present invention. It should be noted that the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0043] Example 1

[0044] Li2CO3, Al2O3 and SiO2 powders were mixed in a molar ratio of 1:1:2, and ball milled in anhydrous ethanol dispersion medium using a high-energy ball mill, with zirconium oxide as the grinding ball, at a speed of 400rpm, for 2 hours to obtain a mixture. After the mixture was evaporated and dried, it was placed in a sintering furnace at a sintering temperature of 800℃ and a holding time of 8 hours to obtain a pre-sintered body. The pre-sintered body was crushed again, placed in a tableting mold with a diameter of 10mm, and pressed into tablets at a pressure of 200Mpa for 10 minutes, and then sintered in a sintering furnace at 1200℃ for 8 hours, and cooled with the furnace to obtain a LiAlSiO4 solid electrolyte.

[0045] The LiAlSiO4 solid electrolyte was subjected to AC impedance and electrochemical window tests using an electrochemical workstation, and its ionic conductivity at 25°C was found to be 1.3×10 -3 S / cm, and the electrochemical window is 5 V (see Table 1).

[0046] Example 2

[0047] Li2CO3, ZnO and SiO2 powders were mixed in a molar ratio of 1:1:1, and ball milled in anhydrous ethanol dispersion medium using a high-energy ball mill, with zirconium oxide as the grinding ball, at a speed of 400rpm, for 2 hours to obtain a mixture. After the mixture was evaporated and dried, it was placed in a sintering furnace at a sintering temperature of 800℃ and a holding time of 8 hours to obtain a pre-sintered body. The pre-sintered body was crushed again, placed in a tableting mold with a diameter of 10mm, and pressed into tablets at a pressure of 200Mpa for 10 minutes, and then sintered in a sintering furnace at 1200℃ for 8 hours, and cooled with the furnace to obtain a Li2ZnSiO4 solid electrolyte.

[0048] The Li2ZnSiO4 solid electrolyte was subjected to AC impedance and electrochemical window tests using an electrochemical workstation, and its ionic conductivity at 25°C was found to be 3.1×10 -3 S / cm, and the electrochemical window is 5 V (see Table 1).

[0049] Example 3

[0050] Li2CO3, Ga2O3 and ZrO2 powders were mixed in a molar ratio of 1:1:2, and ball milled in anhydrous ethanol dispersion medium using a high-energy ball mill, with zirconium oxide as the grinding ball, at a speed of 400rpm, for 2 hours to obtain a mixture. After the mixture was evaporated and dried, it was placed in a sintering furnace at a sintering temperature of 800℃ and a holding time of 8 hours to obtain a pre-sintered body. The pre-sintered body was crushed again, placed in a tableting mold with a diameter of 10mm, and pressed into tablets at a pressure of 200Mpa for 10 minutes, and then sintered in a sintering furnace at 1200℃ for 8 hours, and cooled with the furnace to obtain LiGaZrO4 solid electrolyte.

[0051] The LiGaZrO4 solid electrolyte was subjected to AC impedance and electrochemical window tests using an electrochemical workstation, and its ionic conductivity at 25°C was found to be 5.7×10 -3 S / cm, and the electrochemical window is 5 V (see Table 1).

[0052] Example 4

[0053] Li2CO3, Bi2O3 and GeO2 powders were mixed in a molar ratio of 1:1:2, and ball milled in anhydrous ethanol dispersion medium using a high-energy ball mill, with zirconium oxide as the grinding ball, at a speed of 400rpm, for 2 hours to obtain a mixture. After the mixture was evaporated and dried, it was placed in a sintering furnace at a sintering temperature of 800℃ and a holding time of 8 hours to obtain a pre-sintered body. The pre-sintered body was crushed again, placed in a tableting mold with a diameter of 10mm, and pressed into tablets at a pressure of 200Mpa for 10 minutes, and then sintered in a sintering furnace at 1200℃ for 8 hours, and cooled with the furnace to obtain a LiBiGeO4 solid electrolyte.

[0054] The LiBiGeO4 solid electrolyte was subjected to AC impedance and electrochemical window tests using an electrochemical workstation, and its ionic conductivity at 25°C was found to be 6.3×10 -3 S / cm, and the electrochemical window is 5 V (see Table 1).

[0055] Example 5

[0056] Li2CO3 and Ga2O3 powders were mixed in a molar ratio of 1:5, and ball milled in anhydrous ethanol dispersion medium using a high-energy ball mill, with zirconium oxide as the grinding ball, at a speed of 400rpm, for 2 hours to obtain a mixture. After the mixture was evaporated and dried, it was placed in a sintering furnace at a sintering temperature of 800°C and a holding time of 8 hours to obtain a pre-sintered body. The pre-sintered body was crushed again, placed in a tableting mold with a diameter of 10 mm, and pressed into tablets at a pressure of 200Mpa for 10 minutes, and then sintered in a sintering furnace at 1200°C for 8 hours, and cooled with the furnace to obtain a LiGa5O8 solid electrolyte.

[0057] The LiGa5O8 solid electrolyte was subjected to AC impedance and electrochemical window tests using an electrochemical workstation, and its ionic conductivity at 25°C was found to be 7.2×10 -3 S / cm, and the electrochemical window is 5 V (see Table 1).

[0058] Example 6

[0059] Li2CO3 and Ga2O3 powders were mixed in a molar ratio of 1:1, and ball milled in anhydrous ethanol dispersion medium using a high-energy ball mill, with zirconium oxide as the grinding ball, at a speed of 400rpm, for 2 hours to obtain a mixture. After the mixture was evaporated and dried, it was placed in a sintering furnace at a sintering temperature of 800°C and a holding time of 8 hours to obtain a pre-sintered body. The pre-sintered body was crushed again, placed in a tableting mold with a diameter of 10 mm, and pressed into tablets at a pressure of 200Mpa for 10 minutes, and then sintered in a sintering furnace at 1200°C for 8 hours, and cooled with the furnace to obtain a LiGaO2 solid electrolyte.

[0060] The LiGaO2 solid electrolyte was subjected to AC impedance and electrochemical window tests using an electrochemical workstation, and its ionic conductivity at 25°C was found to be 8.4×10 -3 S / cm, and the electrochemical window is 5 V (see Table 1).

[0061] Example 7

[0062] Li2CO3 and Ga2O3 powders were mixed in a molar ratio of 5:1, and ball milled in anhydrous ethanol dispersion medium using a high-energy ball mill, with zirconium oxide as the grinding ball, at a speed of 400rpm, for 2 hours to obtain a mixture. After the mixture was evaporated and dried, it was placed in a sintering furnace at a sintering temperature of 800°C and a holding time of 8 hours to obtain a pre-sintered body. The pre-sintered body was crushed again, placed in a tableting mold with a diameter of 10 mm, and pressed into tablets at a pressure of 200 MPa for 10 minutes, and then sintered in a sintering furnace at 1200°C for 8 hours, and cooled with the furnace to obtain a Li5GaO4 solid electrolyte.

[0063] The Li5GaO4 solid electrolyte was subjected to AC impedance and electrochemical window tests using an electrochemical workstation, and its ionic conductivity at 25°C was found to be 9.5×10 -3 S / cm, and the electrochemical window is 5 V (see Table 1).

[0064] Example 8

[0065] Except that the pre-sintering temperature was adjusted to 500° C., other methods and conditions were the same as those in Example 1.

[0066] Example 9

[0067] Except that the pre-sintering temperature was adjusted to 1050° C., other methods and conditions were the same as those in Example 1.

[0068] Example 10

[0069] Except that the pressure was adjusted to 120 MPa, other methods and conditions were the same as those in Example 1.

[0070] Embodiment 11

[0071] Except that the pressure was adjusted to 260 MPa, other methods and conditions were the same as those in Example 1.

[0072] Table 1 Ionic conductivity and electrochemical window of oxide solid electrolytes

[0073]

[0074] From the comparison of Example 1, Example 8 and Example 9 in Table 1, it can be seen that a pre-sintering temperature that is too high or too low will affect the crystallinity of the solid electrolyte, thereby ultimately affecting the electrochemical performance.

[0075] From the comparison of Example 1, Example 10 and Example 11 in Table 1, it can be seen that too high or too low compression stress will affect the density of the solid electrolyte, thereby ultimately affecting the electrochemical performance.

[0076] Therefore, appropriate pre-sintering temperature and pressing stress are the prerequisites for solid electrolytes to achieve optimal crystallinity and density, and are also important conditions for solid electrolytes to have excellent electrochemical properties.

[0077] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

[0078] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An oxide solid electrolyte, characterized in that: The oxide solid electrolyte is crystalline, and the chemical composition of the oxide solid electrolyte includes LiGaZrO4; The oxide solid electrolyte has a single component and an impurity content of less than 0.05%.

2. The oxide solid electrolyte according to claim 1, characterized in that The oxide solid electrolyte includes LiGaZrO4, and the molar ratio of Li, Ga and Zr is 1:1:

1.

3. The oxide solid electrolyte according to claim 1 or 2, characterized in that: The raw material source of the oxide solid electrolyte is any one of carbonate, oxide or hydroxide, or a combination of at least two of them.

4. The method for preparing an oxide solid electrolyte according to any one of claims 1 to 3, characterized in that: The method is a high temperature solid phase method, comprising: (1) weighing raw materials according to the molar ratio of the oxide solid electrolyte chemical formula, mixing and wet ball milling; (2) evaporative drying; (3) Pre-sintering; (4) Crushing, tableting and re-sintering.

5. The method according to claim 4, characterized in that The raw material in step (1) is any one of carbonate, oxide or hydroxide, or a combination of at least two of them.

6. The method according to claim 4, characterized in that The wet ball milling in step (1) comprises: mixing the raw materials, using alcohol as a dispersion medium and ball milling balls as ball milling media, and performing wet ball milling.

7. The method according to claim 4, characterized in that The time of the wet ball milling in step (1) is 2 to 8 hours.

8. The method according to claim 4, characterized in that The pre-sintering temperature in step (3) is 700-900°C.

9. The method according to claim 4, characterized in that The pre-sintering temperature in step (3) is 800-900°C.

10. The method according to claim 4, characterized in that The pre-sintering time in step (3) is 2 to 8 hours.

11. The method according to claim 4, characterized in that The crushing in step (4) is high-energy crushing.

12. The method according to claim 4, characterized in that The crushing in step (4) is high-energy ball milling.

13. The method according to claim 4, characterized in that The tabletting pressure in step (4) is 190-220 MPa, and the pressure holding time is 5-10 min.

14. The method according to claim 4, characterized in that The sintering temperature in step (4) is 1100-1300° C. and the sintering time is 2-8 hours.

15. The method according to claim 4, characterized in that The sintering temperature in step (4) is 200 to 400° C. higher than the pre-sintering temperature in step (3).

16. The method according to claim 4, characterized in that The method comprises the following steps: (1) weighing raw materials according to the molar ratio of the oxide solid electrolyte chemical formula, mixing, using anhydrous ethanol as a dispersion medium and zirconium oxide grinding balls as a ball milling medium, and wet-milling for 2 to 8 hours to obtain a slurry; (2) evaporative drying; (3) Pre-sintering in a sintering furnace at 700-900°C for 2-8h; (4) The pre-sintered material is crushed into powder by high-energy ball milling, pressed into tablets under a pressure of 190 to 220 MPa for 5 to 10 minutes, and then placed in a sintering furnace at 1100 to 1300°C for 2 to 8 hours.

17. Use of the oxide solid electrolyte according to any one of claims 1 to 3 in a solid-state battery.

Citation Information

Patent Citations

  • Preparation method of lithium ion battery solid electrolyte material Li7La3Zr2O12

    CN103594725A

  • Preparation method for all-solid-state lithium ion electrolyte material Li7La3Zr2O12

    CN105406117A

  • Method for preparing solid-state lithium-ion electrolyte material Li<7>La<3>Zr<2>O<12> by molten-salt growth method

    CN105489930A

  • Solid electrolyte for lithium ion battery, preparation method for solid electrolyte, and lithium ion battery

    CN104953175A

  • An interface infiltrated quasi-solid alkali metal cell, electrodes of the cell and a preparing method of the cell

    CN105374980A